Social Responsibility of the Higher Education Institutions and Remote Social Audit - Peicheva, Miroslava (Research Papers, 2021)
The role of higher education institutions is crucial for the development of social responsibility. And this is because they educate and bring up current and future leaders who will make decisions in an unstable socio-economic environment. Therefore, all stakeholders need an independent assessment provided by the remote social audit.The main goal of the present study is to analyze the social responsibility of higher education institutions and to develop a model for remote social audit. To achieve this goal, the following tasks have been performed: social responsibility, including of higher education institutions, has been analyzed, a model with good practices on social responsibility of higher education institutions, which can be used as a standard in conducting remote social audit in them has been developed. ; a model for remote social audit of higher education institutions has been developed. The scientific methods of analysis, synthesis, induction, deduction were used in the research.The main results show that the world’s leading universities have socially responsible behavior, conduct social initiatives and communicate their socially responsible behavior with all stakeholders. With regard to social audit, the results show that remote social audit has a number of advantages over traditional social audit.Limitations of the research: The results presented in this study are only part of a bigger study (Peicheva, 2019), dedicated to the social responsibility of higher education institutions and remote social audit. The higher education institutions analyzed in the study are in: China, Russia and Bulgaria.The uniqueness of the present research is expressed in the development of a model with good practices for social responsibility of higher education institutions and a model for remote social audit.